Pengelolaan Keuangan Keluarga Secara Islam Pada Keluarga Muslim Etnis Padang Dan Makassar Di Surabaya - Rosalia Debby Endrianti; Nisful Laila (Universitas Airlangga, 2016)
The goal of this research is understanding how does management financial implementation work into Muslim Family, especially at Padang and Makassar ethnics in Surabaya.This research used descriptive qualitative approach. Data collection was resulted by interview, observation, and documentation. Domain and taxonomy technique was used to perform data analytic. This technique to find the general description of financial management family work into Muslim then elaborated more detail to know the internal structure of Islamic view of wealth, the provision, determine the priority scale, and make budget household.The results based on interviews with two informants from the Padang and Makassar is both informants in research has implemented most components financial management to reach sakinah finance in the life daily. The financial management component are Islamic view of wealth, the provision, determine the priority scale, and make budget household.